(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Transnationalism generates connections between people, societies, and nations, as well as changes in the social, economic, and cultural lives of both the origin and destination countries. The purpose of this article is to look at the impact of people movement, technology, and trade on modern life, society, culture, and literature. It focuses on experiences that transcend national, racial, and linguistic borders. "Someone who expands and goes beyond national limits," Merriam Webster defines transnational as "someone who extends and goes beyond national boundaries" (Webster). The prefix Trans, which means "across," "beyond," and "outside of," is a Latin preposition. As a result, transnational refers to something that exists outside of a nation. Nation is a word that comes from the Latin word natio and refers to an imagined polity that exists inside a defined territory. The modern-nation notion, according to Tölölyan, is unquestionably a product of the Enlightenment era, and it has now transformed due to population dispersal.